Valorization of waste biomass from northeastern Brazil’s June festivals: adsorption of two textile dyes for environmental remediation and residue reutilization - Costa, José Arnaldo S. [UNESP]; Oliveira, Rhayza Victoria M.; Maia, Hermógenes B.; Gomes, Pricília S. P.; Romão, Luciane P. C. [UNESP] (Springer Nature, 2023)
In the present approach, we strategically use the Junina triad (named corn, coconut, and peanut husks) in an ambient remediation system for different textile reactive dyes. The remediation of Procion Yellow H-E 3G and Acid red 114 dyes by the Janina triad was conducted from the statistical treatment (24). The XRD analyses revealed the presence of the amorphous carbonaceous nature of the biomasses, which are mainly composed of carbon and oxygen, typical of fibrous surfaces, such as the biomasses used, according to the SEM-EDS analysis. FTIR analysis of the biomasses exhibited the presence of a variety of oxygenated and electron-rich functional groups, which were useful for the remediation of dyes. Statistical optimization showed that the solution pH is the effect that most influences in the adsorption of the two dyes by the Junina triad. On the other hand, a high removal percentage of Procion Yellow H-E 3G and Acid red 114 was observed in the first 5 min of adsorption, especially in experiment 13 (for the corn and coconut husks in the Procion Yellow H-E 3G removal), as well as experiments 1 and 13 (for the peanut and coconut husks in the Acid red 114 remediation, respectively. Finally, we highlight the advanced adsorptive properties presented by the Junina triad for the use in environmental samples, whose removal efficiency values varied between: (i) 87.04–97.94% for the Procion Yellow H-E 3G and 85.53–95.09% for the Acid red 114 by the corn husk; (ii) 44.30–75.52% and 90.73–92.16% in the Procion Yellow H-E 3G and Acid red 114 removal, respectively, by the coconut husk; and (iii) 81.50–86.61% (Procion Yellow H-E 3G) and 60.36–65.65% (Acid red 114) using the peanut husk.Graphical abstract